Genotype-environment interaction of genotypes of cocoa in Mexico - Carlos Hugo Avendaño-Arrazate; Misael Martínez-Bolaños; Ana Laura Reyes-Reyes; Marco Aurelio Aragón-Magadán; Delfino Reyes-López; Fernando López-Morales (Scientific Reports)
Abstract Cacao (Theobroma cacao L.) production is significantly influenced by genotype-environment interactions, which affect key agronomic traits such as yield, fruit quality, and disease resistance. Despite advances in cacao breeding, one of the main challenges remains the identification of stable, high-performing clones that can adapt to different environmental conditions while maintaining desirable agronomic characteristics. In particular, the introduction of improved clones with high productivity and tolerance to diseases such as frosty pod rot is essential to ensure sustainable production. However, limited information exists on the environmental influence on these traits, making it crucial to assess the performance of new cacao clones in diverse agroecological conditions before their large-scale adoption. With the objective of evaluating the genotype-environment interaction of cacao clones generated by INIFAP and introduced for their tolerance to diseases (frosty pod rot), high yield, and quality, 23 cacao clones were established in three environments: (1) Campo Experimental Rosario Izapa-Tuxtla chico, Chiapas; (2) Ejido Umoa, Tapachula, Chiapas y (3) Vicente Guerreo, Teapa, Tabasco. The cacao clones were established in a Randomized Block Experimental Design with three replications and five trees per block. Statistical analysis was conducted in R 4.4.1 using the statgenGxE package and hierarchical clustering. The variance analysis showed highly significant differences among the genotypes for all the evaluated variables, indicating considerable genetic variability in terms of fruit length (FL), fruit weight (FW), total number of seeds (TNS), individual seed dry weight (ISDW), and pod index (PI). Environment 1, located in Rosario Izapa, Chiapas, stood out as the best for the variables FL, TNS, and ISDW. On the other hand, environment 3, situated in Vicente Guerrero, Teapa, Tabasco, proved to be the most suitable for FW and PI. In contrast, environment 2, located in Ejido Umoa, Tapachula, Chiapas, ranked as the worst for most of the variables, particularly for FL, FW, and TNS. The sensitivity analysis of the cacao genotypes depended on the type of variable; for the fruit variables, genotype 5 stood out for FL, genotype 18 for FW, genotype 4 for TNS, genotype 9 for ISDW, and genotype 15 for PI. In general, the best genotype for fruit variables was genotype 25 (F19P3). Finally, it was observed that among the 23 promising cacao genotypes, most exhibited interaction with the environment, suggesting that it is very important to consider the environmental conditions where the varieties will be established. The findings of this study provide valuable insights into the influence of environmental conditions on cacao productivity and quality, highlighting the need for site-specific clone selection. The identification of high-yielding and stable genotypes can facilitate more efficient breeding strategies and better decision-making for cacao producers and researchers. By understanding how different environments impact agronomic traits, this research contributes to the sustainable intensification of cacao cultivation, helping to optimize yields while mitigating the risks associated with environmental variability. These results are particularly relevant for breeding programs aimed at developing resilient cacao varieties suited to diverse agroecological regions.